Smart Energy Home Management Using Hybrid system - et.al, Vigneshwaran Perumal (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Energy balance is one of the main criteria to operate the grid in stable condition. If there is any energy imbalance occurs due to increase in demand then the grid will not operate in stable condition. Increase demand is one of the major issues facing by grid. To address this problems many countries promoting the renewable energy generation this will support the grid to avoid energy imbalance problem. Prosumerplay a key role in this situation, where they can utilize the generated energy and remaining surplus power can integrate it to the grid. While utilising the renewable power generate it should be controlled and monitored effectively so that we can reduce the tariff cost. Solar panels installed in house need to bemonitored continuously to improve the performance of battery. In this paper, the power line communication (PLC) compliant with Home Plug is implementing to check energy consumption. The system design is composed of three components: Driver circuit, ac supply, and smart device application. This system will switch over from solar energy consumption to AC supply according to the load requirement. This scheme will maintain the performance of a PV system and contribute to enhancing home energy management system. The system design was stimulated with Matlaband verified with the hardwareresults.